Design of Networked Computer Learning Applications for Android-Based Beginners - Firdaus Firdaus; Muhammad Iqbal (Institute of Computer Science (IOCS), 2022)
Learning applications are media that can be used to convey material content involving mobile devices such as Android-based mobile phones. Computer Network is a collection of computers, as well as other supporting computer devices that are connected to each other in a single unit. In this final project, a networked computer learning media application is designed for smartphones, especially Android using the Java programming language, where there are materials and quizzes including lessons about network computers. This application can only run on smartphones based on the Android operating system.